2003
DOI: 10.1128/jb.185.14.4256-4267.2003
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosisChaperonin 10 Is Secreted in the Macrophage Phagosome: Is Secretion Due to Dissociation and Adoption of a Partially Helical Structure at the Membrane?

Abstract: To confirm that Mycobacterium tuberculosis chaperonin 10 (Cpn10) is secreted outside the live bacillus, infected macrophages were examined by electron microscopy. This revealed that the mycobacterial protein accumulates both in the wall of the bacterium and in the matrix of the phagosomes in which ingested mycobacteria survive within infected macrophages. To understand the structural implications underlying this secretion, a structural study of M. tuberculosis Cpn10 was performed under conditions that are gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 50 publications
4
23
0
Order By: Relevance
“…Levels of sequence identity with GroEL of more than 50% for both the proteins suggest that these proteins might also function as molecular chaperones in M. tuberculosis. Interestingly, the mycobacterial chaperonins have previously been shown to be secreted into the extracellular environment, although their role as molecular chaperones is limited to the cytosol (10,14). The existence of chaperonins in the extracellular environment thus suggests a possible alternate functional role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Levels of sequence identity with GroEL of more than 50% for both the proteins suggest that these proteins might also function as molecular chaperones in M. tuberculosis. Interestingly, the mycobacterial chaperonins have previously been shown to be secreted into the extracellular environment, although their role as molecular chaperones is limited to the cytosol (10,14). The existence of chaperonins in the extracellular environment thus suggests a possible alternate functional role.…”
Section: Discussionmentioning
confidence: 99%
“…However, translation searches with this orientation and with different models did not yield a satisfactory solution. The best solution for the translation function was obtained by using the E. coli 14 complex structure (Protein Data Bank code 1KP8) as the model. The 1KP8 model was oriented according to the common orientation at the start of translation searches.…”
Section: Resultsmentioning
confidence: 99%
“…LPS was removed by passing the protein through a polymyxin B-agarose column (Detoxigel column; Pierce, Rockford, IL). The fusion protein of HSP65 and PSA peptide (HSP65-PSA) [32] and the fusion protein of Chap10 and MUC1 peptide (Chap10-MUC1) [33] were prepared similarly as described above. The MUC1-derived peptide (NH 2 -SAPDTRPAP) and the PSA-derived peptide (NH 2 -FLTPKKLQCV) were synthesized using standard F-moc chemistry on a peptide synthesizer (model 432A; PE Applied Biosystems).…”
Section: Preparation Of Recombinant Proteins and Peptidesmentioning
confidence: 99%
“…HSP10 (GroES), a cochaperonin to HSP60 (GroEL) shared the same GroE operons and co-expressed the GroE complex with HSP60. It is located in cytosol, cell membrane, intercellular space, and periphery with mounting evidence demonstration (Fossati et al 2003;Jia et al 2011) and may interact with various surrounding environment. The association between the presence of anti-HSP10 antibodies and adult onset asthma or Chlamydia trachomatis genital tract infection (Betsou et al 1999;LaVerda et al 2000;Betsou et al 2003) indicated that CHSP10 had been exposed to the host components and triggered the immune system to produce the specific anti- Figure 7.…”
Section: Discussionmentioning
confidence: 97%